The Modern city readings in urban economics - Rasmussen, David W.; Haworth, Charles T. (Harper & Row, 1973)
This text considers basic issues of urban economics within the context of problems faced by a modern industrial society. Concepts of economic theory that bear on urban public policy are discussed early in the book. The chapters that follow deal with poverty, central city decay, the location of urban economic activity, housing and urban renewal, urban transportation, the urban public sector, and the optimum size for a city.